The Golden Ratio: A Mathematical and Aesthetic Marvel - Subedi, Shantiram (Damak Campus Journal, 2024)
The Golden Ratio, approximately 1.618, is a mathematical constant that has captivated the imagination of scholars, artists, architects, and scientists for centuries. This article delves into the mathematical underpinnings of the Golden Ratio, tracing its origins and historical significance in ancient civilizations and its evolution in mathematical theory. Known for its unique properties, the Golden Ratio is often associated with beauty, balance, and harmony, which has led to its widespread application in diverse fields. From the design of iconic architectural marvels like the Parthenon to its presence in Renaissance art, the Golden Ratio continues to inspire creativity. It also manifests in nature, evident in the arrangement of leaves, the spiral patterns of shells, and the structure of galaxies. In modern science, the Golden Ratio finds relevance in engineering, computer algorithms, and even financial models. This exploration underscores its enduring allure, showcasing its theoretical elegance and practical utility across time and disciplines